(3efXheI GddGejI GdeTghQI aj Yde GdRGjQLIs - (3CHhGdYHGS CMeO GdSHJjs
(3ChdgG (B:s
(3HGSeGFc GdMSfi hCSFdc GdJhajb ddYde s
(3BNQgG (B:s
(3hbO Jfe BNQ eG hLO ef gPg GdefXheI GdHOjYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B53s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B949s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(58) s
Keywords: (3GdMQha h GdChaGbs